PENINGKATAN HASIL BELAJAR SISWA TENTANG ENERGI DAN PERPINDAHAN PANAS DENGAN METODE INQUIRY - Junaidi; Haryono; Handayani, Monika (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
As an elementary school teacher, we sometimes encounter problems in learning science. Through reflection activities, the teacher realized that in class IV SDN 3, Karangrandu's mastery of Energy and Heat Transfer material was still low. In the 2022/2023 academic year, out of 30 students, only ten students, or around 33% of students, achieved the minimum standard of completeness. To increase learning outcomes, a class action research step is needed through the inquiry method. The subjects of this classroom action research were students in class IV of SDN 3 Karangrandu, Pecangaan District, Jepara Regency, with 30 students recorded, with details of 20 female students and ten male students. This improvement in science learning will be carried out in the 2022/2023 academic year semester I for class IV. Research on pre-cycle found that 33% of students completed it. Then, in the first cycle of learning improvement, there was another increase, which was proven by the evaluation results of students who reached 77% and the KKM. Finally, cycle II improved the skills and understanding of Energy and Heat Transfer, and students can mention examples of conduction, convection, and radiation. Twenty-eight students obtained a score range of 70-80, meaning their completeness level reached 94%.